Membrane Bioreactor: Applications and Limitations in Treating High Strength Industrial Wastewater - Noor Sabrina, Ahmad Mutamim; Zainura, Zainon Noor; Mohd Ariff, Abu Hassan; Yuniarto, Adhi; Olsson, Gustaf (Elsevier, 2013)
This paper reviewed the application of membrane bioreactor in treating high strength industrial wastewater by analysing operational parameters, limitations and mitigations of MBR for industrial wastewater. High strength industrial wastewater is difficult to classify but by its characteristics can be predicted using biodegradability criteria (BOD5/COD). Several factors need to be taken into consideration to find suitable operating parameters such as hydraulic retention time (HRT), solid retention time (SRT), mix liquor suspended solid (MLSS), food to microorganism (F/M), transmembrane pressure (TMP) and Flux (J) to obtain good quality effluent and reduce the fouling effect. Fouling factors by membrane, biomass and MBR operation need to be taken seriously because they are the major problems affecting the performance of the MBR and quality of the effluent. There are specific methods to reduce and clean the clogging membrane depending on the level of severity of the fouling. The mitigation covers physical cleaning such as membrane relaxing, backwashing, a combination of both and chemical cleaning which is used for irreversible fouling. In some cases, modification of MBR is needed to improve the performance and to achieve high quality of effluent.